1987
DOI: 10.1017/s0043174500060471
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and Germination of Crownbeard (Verbesina encelioides)

Abstract: Crownbeard [Verbesina encelioides(Cav.) Benth. & Hook. f. ex. A. Gray # VEEEN (Compositae)] exhibited rapid seedling, vegetative, and reproductive growth. Seed germination under ideal conditions was high and occurred in varying soils except in gravel. It was significantly suppressed under drought and waterlogged conditions and was maximum at 21% moisture regimes. Larger and heavier seeds which exhibited higher germination were produced by the plants growing in open and sand dune habitats. Seedling emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…4). This species grows to a larger maximum size than any of the other species in our communities (120 cm tall), and is a successful weed pest in North America and India (Kaul & Mangal 1987). Thus it is not surprising that this species dominated the biomass production in our communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). This species grows to a larger maximum size than any of the other species in our communities (120 cm tall), and is a successful weed pest in North America and India (Kaul & Mangal 1987). Thus it is not surprising that this species dominated the biomass production in our communities.…”
Section: Discussionmentioning
confidence: 99%
“…It forms numerous pure stands and establishes itself in a variety of habitats. High and rapid seed germination (up to 94%), efficient seedling survival, quick vegetative and reproductive growth, extensive seed production, efficient self‐ and cross‐pollination, and broad ecological amplitude have contributed to the biological success of this species (Kaul & Mangal 1987).…”
Section: Methodsmentioning
confidence: 99%
“…(2010), rapid growth from vegetative stage through to flowering stage and high seed production are among the ideal characteristics of invasive weeds. Furthermore, its winged achenes are easily dispersed by light winds (Kaul & Mangal 1987). Results showed that the weed is not yet widespread in Tunisia.…”
Section: Subspecies Distinguishing Featuresmentioning
confidence: 98%
“…Specimens were collected from the infested habitat and examined to identify the species based on dichotomous genus and species keys of the Asteraceae (Haines 2011), relevant literature (Parker 1972;Kaul & Mangal 1987;Wagner & al. 1990;Taleb & Bouhache 2006) and online databases (e.g.…”
Section: Species and Subspecies Identificationmentioning
confidence: 99%
See 1 more Smart Citation